Robot-assisted esophagectomy may improve perioperative outcome in patients with esophageal cancer – a single-center experience - Betzler, Johanna; Elfinger, Lea; Büttner, Sylvia; Weiß, Christel; Rahbari, Nuh; Betzler, Alexander; Reißfelder, Christoph; Otto, Mirko; Blank, Susanne; Schölch, Sebastian (Frontiers in Oncology, 2022)
Background: Although the introduction of minimally invasive surgical techniques has improved surgical outcomes in recent decades, esophagectomy for esophageal cancer is still associated with severe complications and a high mortality rate. Robot-assisted surgery is already established in certain fields and robot-assisted esophagectomy may be a possible alternative to the standard minimally invasive esophagectomy. The goal of this study was to investigate whether robot assistance in esophagectomy can improve patient outcome while maintaining good oncological control. Material and Methods: Data of all patients who underwent minimally invasive esophagectomy between January 2018 and November 2021 at University Hospital Mannheim was collected retrospectively. Patients were divided into two cohorts according to operative technique (standard minimally invasive (MIE) vs. robot-assisted esophagectomy (RAMIE), and their outcomes compared. In a separate analysis, patients were propensity score matched according to age, gender and histological diagnosis, leading to 20 matching pairs. Results: 95 patients were included in this study. Of those, 71 patients underwent robot-assisted esophagectomy and 24 patients underwent standard minimally invasive esophagectomy. Robot-assisted esophagectomy showed a lower incidence of general postoperative complications (52.1% vs. 79.2%, p=0.0198), surgical complications (42.3% vs. 75.0%, p=0.0055), a lower rate of anastomotic leakage (21.1% vs. 50.0%, p=0.0067), a lower Comprehensive Complication Index (median of 20.9 vs. 38.6, p=0.0065) as well as a shorter duration of hospital stay (median of 15 vs. 26 days, p=0.0012) and stay in the intensive care unit (median of 4 vs. 7 days, p=0.028) than standard minimally invasive surgery. After additionally matching RAMIE and MIE patients according to age, gender and diagnosis, we found significant improvement in the RAMIE group compared to the MIE group regarding the Comprehensive Complication Index (median of 20.9 vs. 38.6, p=0.0276), anastomotic leakage (20% vs. 55%, p=0.0484) and severe toxicity during neoadjuvant treatment (0 patients vs. 9 patients, p=0.005). Conclusion: Robot-assisted surgery can significantly improve outcomes for patients with esophageal cancer. It may lead to a shorter hospital stay as well as lower rates of complications, including anastomotic leakage.